Hantavirus in the peruvian jungle: a systematic review of series and cases reported: Hantavirus en la selva peruana: una revisión de casos - Saavedra Velasco, Marcos (2021)
Hantavirosis is a zoonotic infection transmitted mainly by rodents. In Peru, a lethality of 40–60% is calculated in inhabitants of the Peruvian Amazon jungle, especially in Loreto. Despite this, this disease continues to be under-diagnosed despite the fact that it represents a serious problem for public health in Latin America. We present a sistematic revision of case reports and seris of cases of Hantavirus infection in the Peruvian jungle. The most important characteristic of the cases presented are mean age 25.7 years, predominance of females (5/6), clinical presentation of headache, myalgias, nausea and vomiting (6/6) and unfavorable evolution to acute respiratory to acute respiratory distress (ARDS), renal failure, septic shock and multiple organ failure in 3of the cases presented.